SPORT FACILITIES - SPORT ACTIVITIES HARDWARE - Zoran Mašić; Vadislav Ilić; Filanti Agelaku (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Realisation of sport activities always demanded certain conditions. Among those, sports facilities are certainly necessary. Since there were important changes in the process of training itself and successful performance, as well as, the results achieved by the sportsmen; there is a need for adequate sports facilities, that include whole variety of systems,equipment and necessities. Nowadays, Sport facilities are not only "the place of event", but also a condition/necessity in achieving best sport results. It is demanded that these facilities are comfortable, absolutely secure and that they can accommodate transmissions: an opening, the course of sports activities and the announcement of the winner. The kind of sport activity, age, sex; so the "sports level" of the competitors is emphasising the specific demands to wards sports facilities.